Phosphatase of Regenerating Liver-1 (PRL-1) Regulates Actin Dynamics During Immunological Synapse Assembly and T Cell Effector Function - Castro-Sánchez, Patricia; Ramirez-Munoz, Rocío; Martín-Cófreces, Noa B.; Aguilar-Sopeña, Oscar; Alegre-Gomez, Sergio; Hernández-Pérez, Sara; Reyes, Raquel; Zeng, Qi; Cabañas, Carlos; Sánchez-Madrid, Francisco; Roda-Navarro, Pedro (Frontiers in Immunology, 2018)
The regulatory role of most dual specific phosphatases during T cell activation remains unknown. Here, we have studied the expression and function of phosphatases of regenerating liver (PRLs: PRL-1, PRL-2, and PRL-3) during T cell activation, as well as, the dynamic delivery of PRL-1 to the Immunological Synapse (IS). We found that T cell activation downregulates the expression of PRL-2, resulting in an increased PRL-1/PRL-2 ratio. PRL-1 redistributed at the IS in two stages: Initially, it was transiently accumulated at scanning membranes enriched in CD3 and actin, and at later times, it was delivered at the contact site from pericentriolar, CD3ζ-containing, vesicles. Once at the established IS, PRL-1 distributed to LFA-1 and CD3ε sites. Remarkably, PRL-1 was found to regulate actin dynamics during IS assembly and the secretion of IL-2. Moreover, pharmacological inhibition of the catalytic activity of the three PRLs reduced the secretion of IL-2. These results provide evidence indicating a regulatory role of PRL-1 during IS assembly and highlight the involvement of PRLs in immune responses by mature T cells.